SOSIALISASI PERAN TEKNOLOGI DALAM MENINGKATKAN INKLUSI DAN LITERASI KEUANGAN MASYARAKAT PEKON AMBARAWA - Fauzi; Yudhistira Ardana; Muhamad Muslihudin (Jurnal PkM Pemberdayaan Masyarakat, 2020)
Literacy and inclusion is a good knowledge for a village and the village community in Pekon Ambarawa, because both of them are able to be used to build financial facilities and infrastructure that are good and quite profitable. In addition, if accompanied by technological sophistication in this globalization era. The Pekon Ambarawa community will have no difficulty in processing and managing finances and can make use of it for various profitable businesses. The people of Pekon Ambarawa are mostly engaged in agriculture, convection and trade. But unfortunately, financial utilization there is still very minimal. Many people still find it difficult to save or invest from the results of these efforts. Therefore, through Community Service will conduct socialization activities to provide knowledge of how easy and safe ways to borrow and save money and invest their finances with the sophistication of existing technology.